Minimizing gap of utility between consumer and producer in a duopoly market considering outsourcing decision, price, and product tolerance - Anindya Rachma Dwicahyani (Production and Manufacturing Research: An Open Access Journal, 2019)
This study comes up with a new insight into the area of pricing strategy to include consumer perspective under duopolistic competition. Two firms with vertically differentiated products are investigated to compete against price and quality. The implication of outsourcing decisions as one operational strategy carried out by a firm that offers a product with lower price and quality is examined. We consider several components of cost, namely in-house production, quality loss, and outsourcing costs. Market share is calculated using the concept of consumer utility and marginal valuation. Since both firms compete in terms of product prices, the optimal prices must be determined to obtain the equilibrium condition. In addition to profit maximization, this model also aims to minimize the gap between consumer and firm utilities. By optimizing the model sequentially, we obtain the optimal solution regarding product prices, dimensional tolerances, and outsource proportion.